(untitled) (Revista de História da UEG (REVHIST), 2020)
The main goal of this paper is to examine the relevance of universities in the establishment of institutions for the preservation of memory and documentation, especially the ones that house photographic archives and deal with preservation policies, listing, classification and that grant access to their catalogs to the public and researches. Here we describe the establishment of the Centro de Memória do Sul de Minas, founded in May of 2000 in a unity of the Universidade do Estado de Minas Gerais – UEMG, in the city of Campanha, MG, with special attention to the Paulino de Araújo Ferreira Lopes house photographic archive. Keywords: History. Memory. House photographic archives. Centro de Memória Cultural – UEMG/Campanha.